Strategies to enhance the scientific-educational productivity of faculty: a comprehensive approach to improving academic outcomes and promoting professional development. - Carolina Pérez-Montoya (Pontificia Universidad Católica del Perú, 2023)
This article proposes a set of strategies aimed at increasing the scientific-educational productivity of faculty, with the goal of improving academic outcomes and promoting professional development. Based on an analysis of the factors influencing productivity, measures such as continuous training, fostering research, inter-institutional collaboration, and comprehensive evaluation of teaching activities are suggested. These strategies aim not only to strengthen the pedagogical and scientific competencies of faculty but also to create an academic environment that fosters innovation and knowledge transfer. This comprehensive approach has the potential to transform educational quality and contribute to the development of more dynamic and competent educational communities.
Estrategias para potenciar la productividad científico-educacional del profesorado: un enfoque integral para mejorar los resultados académicos y promover el desarrollo profesional
Esta ponencia propone un conjunto de estrategias orientadas a incrementar la productividad científico-educacional del profesorado, con el objetivo de mejorar los resultados académicos y fomentar el desarrollo profesional docente. A partir de un análisis de los factores que condicionan dicha productividad, se sugieren estrategias de gestión como la capacitación continua, el fomento a la investigación, la colaboración interinstitucional y la evaluación integral de las actividades docentes. Estas estrategias no solo buscan fortalecer las competencias pedagógicas y científicas del profesorado, sino también crear un entorno académico que favorezca la innovación y la transferencia de conocimiento. Este enfoque integral tiene el potencial de transformar la calidad educativa y contribuir al desarrollo de comunidades educativas más dinámicas y competentes.
Keywords: academic-educational productivity; professional development of faculty; management strategies; educational research; educational quality